2000
DOI: 10.1002/1097-0088(200007)20:9<969::aid-joc519>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

A catalogue and a classification of surface cyclones for the Western Mediterranean

Abstract: The Mediterranean Sea is a region that possesses a high frequency of cyclones. Many of them are lee depressions and so, mesoscale and weak, but others are strong and cover a wide area. In this study some characteristics of surface cyclones in the Western Mediterranean are presented. First a database was built from hand analyses of sea‐level pressure from 1992 to 1995. Next, a similar database was obtained from the LAM‐INM (Limited Area Model of the Instituto Nacional de Meteorología of Spain) objective analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 6 publications
1
35
0
Order By: Relevance
“…S2). The scarce summer HR events are caused by convective storms, a consequence of thermal related low pressure over the Iberian Peninsula12.…”
Section: Resultsmentioning
confidence: 99%
“…S2). The scarce summer HR events are caused by convective storms, a consequence of thermal related low pressure over the Iberian Peninsula12.…”
Section: Resultsmentioning
confidence: 99%
“…In summer it is generally weaker than in fall and winter and can sometimes combine with sea breeze [ Bastin et al , , ; Drobinski et al , ]. The mistral is frequently observed to extend as far as a few hundred kilometers from the coast [ Jansá , ; Salameh et al , ] and is one of the primary causes of storms over the Mediterranean [ Trigo et al , ; Campins et al , ]. The mistral is often associated with the tramontane, a companion wind which blows from the northwest along the Aude valley between the Pyrénées and the Massif Central [ Georgelin and Richard , ; Drobinski et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…The high frequency and intensity of these winds is a direct consequence of the frequency and intensity of these Mediterranean cyclones [ Lionello et al , 2002]. Cyclogenesis is dependent on the season [ Trigo et al , 1999; Campins et al , 2000; Buzzi and Speranza , 1986; Lionello et al , 2006] and, as suggested by Jansá et al [1994] and Alpert and Ziv [1989], is sustained and intensified by latent heat flux and air‐sea temperature contrast. Low pressure systems can then travel from the Iberian Catalan coast to the Balearic Islands and turn on the GoL where they generate or induce intense local acceleration [ Campins et al , 1995] of the Mistral and Tramontane winds and enhance the air‐sea interactions.…”
Section: Introductionmentioning
confidence: 99%